Collaboration Across Boundaries for Social-Ecological Systems Science Experiences Around the World - Perz, Stephen G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This is a book that any researcher contemplating a large scale interdisciplinary research project investigating social-ecological systems should read. It provides real world tangible examples of such projects and offers lessons that can be used by others to be more successful in their own research efforts." - Robert J Summers, Academic Director, Sustainability Council, University of Alberta, Canada Collaboration across boundaries is widely recognized as a vital requisite for the advancement of innovative science to address problems such as environmental degradation and global change. This book takes collaboration across boundaries seriously by focusing on the many challenges and practices involved in team science when spanning disciplinary, organizational, national and other divides. The authors draw on a shared framework for managing the challenges of collaboration across boundaries as applied to the science of understanding complex social-ecological systems. Teams working across boundaries on diverse social-ecological systems in countries around the world report their challenges and share their practices, outcomes and lessons learned. From these diverse experiences arise many commonalities and also some important differences. These provide the basis for a set of recommendations to any collaborators intending to use science as a tool to better understand social-ecological systems and to improve their management and governance. Stephen G. Perz is Professor in the Department of Sociology and Criminology & Law at the University of Florida, USA. He works collaboratively on conservation and development issues in the Amazon, crossing disciplinary, organizational and national boundaries. This work has been funded by NASA, NSF, USAID, the Moore Foundation, and other sources, and has resulted in over 100 publications in peer-reviewed scholarly outlets.
Preface -- 1. Introduction: Collaboration Across Boundaries for Social-Ecological Systems Science; Stephen G. Perz -- 2. Lessons Learned About Collaborating Across Coupled Natural-Human Systems Research on Mexico's Payments for Hydrological Services Program; Erin C. Pischke, Z. Carter Berry, Randall K. Kolka, Jacob Salcone, Diana Cordoba, Xoco Shinbrot, Sergio Miguel Lopez Ramirez, Kelly W. Jones, Russell G. Congalton, Robert H. Manson, Juan Jose Von Thaden Ugalde, Theresa Selfa, Sophie Avila, Heidi Asbjornsen -- 3. Adapting to the Challenges of International and Interdisciplinary Research of Coupled Human and Natural Systems; Sarah Laborde, Sui Chian Phang, and Mark Moritz -- 4. Collaborative Research across Boundaries: Mangrove Ecosystem Services and Poverty Traps as a Coupled Natural-Human System; Emi Uchida, Victor H. Rivera-Monroy, Sara A. Ates, Edward Castaneda-Moya, Arthur J. Gold, Todd Guilfoos, Mario F. Hernandez, Razack Lokina, Mwita M. Mangora, Stephen R. Midway; Catherine McNally, Michael J. Polito; Matthew Robertson, Robert V. Rohli, Hirotsugu Uchida, Lindsey West, and Xiaochen Zhao -- 5. Learning about Forest Futures under Climate Change through Transdisciplinary Collaboration across Traditional and Western Knowledge Systems; Erica A.H. Smithwick, Christopher Caldwell, Alexander Klippel, Robert M. Scheller, Nancy Tuana, Rebecca Bliege Bird, Klaus Keller, Dennis Vickers, Melissa Lucash, Robert E. Nicholas, Stacey Olson, Kelsey Ruckert, Jared Oyler, Casey Helgeson, and Jiawei Huang -- 6. Sustaining Interdisciplinary Collaboration across Continents and Cultures: Lessons from the Mongolian Rangelands and Resilience Project; María E. Fernández-Giménez, Arren Allegretti , Jay Angerer, Batkhishig Baival, Batbuyan Batjav, Steven Fassnacht, Chantsallkham Jamsranjav, Khishigbayar Jamiyansharav, Melinda Laituri, Robin Reid, Jessica Thompson, Tungalag Ulambayar, Niah Venable -- 7. Challenges of Boundary Crossing in Graduate Training for Coupled Human-Natural Systems Research Elizabeth G. King and Nathan Nibbelink -- 8. Understanding the Central Great Plains as a Coupled Climatic-Hydrological-Human System: Lessons Learned in Operationalizing Interdisciplinary Collaboration; Marcellus Caldas, Martha Mather, Jason Bergtold, Melinda Daniels, Gabriel Granco, Joseph Aistrup, David Haukos, Aleksey Y. Sheshukov, Matthew Sanderson, and Jessica L. Heier Stamm -- 9. High-Resolution Remote Sensing Data as a Boundary Object to Facilitate Interdisciplinary Collaboration; T. Trevor Caughlin, Sarah J. Graves, Gregory P. Asner, Bryan C. Tarbox, and Stephanie A. Bohlman -- 10. Scientists and Stakeholders, Data and Diagnostics: Crossing Boundaries for Modeling the Impacts of Highway Paving in a Tri-national Frontier in the Amazon; Stephen G. Perz, Galia Selaya, Rafael Muñoz-Carpena, Gregory Kiker, Christopher Baraloto, Matthew Marsik and Jane Southworth -- 11. Collaboration across Boundaries: Reflections on Studying the Sustainability of the Mississippi River Delta as a Coupled Natural-Human System; Nina S.-N. Lam, Y. Jun Xu, R. Kelley Pace, Kam-biu Liu, Yi Qiang, Siddhartha Narra, Thomas A. Bianchette, Heng Cai, Lei Zou, Kenan Li, Sanjeev Joshi, and Volodymyr Mihunov -- 12. Crossing Boundaries for Collaboration in Comparative Perspective: Key Insights, Lessons Learned and Recommendations for Future Practice; Stephen G. Perz.
Keywords: Environmental sciences -- Social aspects; Environment; Physical geography; Environmental management; Environmental Social Sciences; Environmental Sciences; Physical Geography; Environmental Management